Chemical Bath Deposition Of Ti-Doped Zno Nanorods For Uv-Photodetector Applications - Bidier, Shaker Ali Hamad Abu (2018)
This work studied the effects of titanium (Ti) on the properties of zinc oxide (ZnO) nanorods (NRs) grown on Si substrates using chemical bath deposition method with TiO2 as a Ti source. X-ray diffraction (XRD) results showed an increase in the crystallite size from 44.4 nm in the undoped sample to 51.2 nm in the doped sample. Photoluminescence results revealed an increment in the energy band gap from 3.241 eV for the undoped sample to 3.293 eV for the doped sample. Hall effect measurements also showed an enhancement in the electrical properties of doped samples, the carrier concentration increased from 8.7×1016 cm-3 for the undoped sample to 2.1×1018 cm-3 for the doped sample.